2012
DOI: 10.2174/157488612800492726
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive and Compulsive Behaviors During Dopamine Replacement Treatment in Parkinson’s Disease and Other Disorders

Abstract: Impulsive and compulsive behaviors, including pathologic gambling, hypersexuality, compulsive shopping, compulsive eating, excessive engagement in hobbies, punding, and Dopamine Dysregulation Syndrome (DDS), are increasingly reported serious side-effects of dopaminergic medication, used in the treatment of Parkinson's Disease (PD) and other disorders. Dopamine Agonists (DA) are strongly related with Impulse Control Disorders (ICDs), while L-dopa is associated with DDS. The present paper focuses on ICDs. The es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 158 publications
(260 reference statements)
1
37
0
4
Order By: Relevance
“…The work tiers from clinical, pathological to genetic and molecular efforts were intended to improve the accuracy of diagnosis for PD, especially for those with probable PD [4]. Although dopamine-replacing agents such as levodopa and dopamine agonists (DAs) improve motor function [5], they also have certain undesired side effects, such as neuropsychiatric symptoms [6] and valvular heart disease [7]. Epidemiologic discussions of this neurodegenerative disease have suggested that tea [8], caffeine and smoking [9] may exert protection against PD, whereas exposure to pesticides may contribute to it [10].…”
Section: Introductionmentioning
confidence: 99%
“…The work tiers from clinical, pathological to genetic and molecular efforts were intended to improve the accuracy of diagnosis for PD, especially for those with probable PD [4]. Although dopamine-replacing agents such as levodopa and dopamine agonists (DAs) improve motor function [5], they also have certain undesired side effects, such as neuropsychiatric symptoms [6] and valvular heart disease [7]. Epidemiologic discussions of this neurodegenerative disease have suggested that tea [8], caffeine and smoking [9] may exert protection against PD, whereas exposure to pesticides may contribute to it [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic medications are known to provoke anxiety, sleep disturbance, compulsion, hypersexuality and restlessness [30,31] . The development of compulsion, such as the loss of control over gambling, alterations in sexual ideation, religious fervor, or craving of illicit substances may not be readily disclosed in the clinical setting and may require special sensitivity and targeted questioning [32,33] . Patients presenting with early drug induced neurotoxicity syndromes are exposed to a wide variety of medical specialists including neurologists, psychiatrists, primary care providers, gastroenterologists and dentists [34] .…”
Section: Neurotoxic Drug Presentationsmentioning
confidence: 99%
“…However, motor complications (dyskinesia) can also appear that are provoked by all dopaminergic medications and these can become treatment limiting (Ahlskog and Muenter, 2001;Nutt, 2001). Dopamine agonists have lower efficacy than L-DOPA and dopamine agonist use is associated with the onset of compulsive behaviours, vascular change, hallucinations and psychosis (Perez-Lloret and Rascol, 2010;Raja and Bentivoglio, 2012). The frequent occurrence of dopaminergic side-effects means that raising the dose of a dopamine agonist when efficacy is insufficient, may not be an option.…”
Section: Introductionmentioning
confidence: 99%